Pengaruh Margin Keuntungan Bersih Dan Arus Kas Bebas Terhadap Pengembalian Saham Sektor Properti Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023 - Fadhil Akmal Ulinuha; M. Kausar Maulana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
The purpose of this study is to determine the effect of net profit margin and free cash flow on stock returns of property sector companies for the 2019-2023 period. This study was conducted using data from the IDX and selected company websites. The population of this study was property sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Sampling was conducted using a purposive sampling technique. The analysis method used was multiple linear regression and simple regression. The results of this study indicate that net profit margin and free cash flow simultaneously affect stock returns. Partially, net profit margin has an effect on stock returns. Partially, free cash flow has no effect on stock returns.